Environmental toxicants human exposures and their health effects - Lippmann, Morton (Wiley-Interscience, 2000)
This authoritative text critically reviews current knowledge on human exposure to selected chemical agents and physical factors in the ambient environment. It provides up-to-date information and research for performing risk assessments.